2021
DOI: 10.6061/clinics/2021/e3015
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity to biological drugs in psoriasis and psoriatic arthritis

Abstract: Monoclonal antibodies or fusion proteins, defined as biological drugs, have modified the natural history of numerous immune-mediated disorders, allowing the development of therapies aimed at blocking the pathophysiological pathways of the disease, providing greater efficacy and safety than conventional treatment strategies. Virtually all therapeutic proteins elicit an immune response, producing anti-drug antibodies (ADAs) against hypervariable regions of immunoglobulins. Immunogenicity against biological drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The frequency of ADAb development in PsA patients treated with ADL is in keeping with previous publications [ 14–17 , 35 ]. However, previous studies draw conflicting conclusions about the effect of csDMARD co-therapy on ADAb production in such patients [ 14 , 15 , 39 ]. A previous smaller study reported a lack of association, highlighting the strength of the larger cohort size in this study [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The frequency of ADAb development in PsA patients treated with ADL is in keeping with previous publications [ 14–17 , 35 ]. However, previous studies draw conflicting conclusions about the effect of csDMARD co-therapy on ADAb production in such patients [ 14 , 15 , 39 ]. A previous smaller study reported a lack of association, highlighting the strength of the larger cohort size in this study [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous smaller study reported a lack of association, highlighting the strength of the larger cohort size in this study [ 14 ]. Conversely, two larger studies, one of which focused on patients with psoriasis, found that concomitant use of immunosuppressors, including MTX, was associated with a reduction in detectable ADAb [ 15 , 39 ]. However, those studies did not investigate whether different csDMARDs had differing effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, there is always potential for immunogenicity for all therapeutic proteins. 33 Although most patients who receive treatment with dupilumab do not develop antibodies against the drug, immunogenicity against a biologic reduces its efficacy and causes treatment-resistant disease. 33 Tralokinumab offers an efficacious alternative in such cases.…”
Section: Relevance To Patient Care and Clinical Practicementioning
confidence: 99%